2008
DOI: 10.1016/j.bbamem.2007.10.027
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of mechanisms of surfactant inhibition

Abstract: Pulmonary surfactant spreads to the hydrated air-lung interface and reduces the surface tension to a very small value. This function fails in acute respiratory distress syndrome (ARDS) and the surface tension stays high. Dysfunction has been attributed to competition for the air-lung interface between plasma proteins and surfactant or, alternatively, to ARDS-specific alterations of the molecular profile of surfactant. Here, we compared the two mechanisms in vitro, to assess their potential role in causing resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 53 publications
2
57
0
Order By: Relevance
“…The search for new drugs of potential clinical interest directed to specific pathologically relevant targets is usually conducted through the analysis of the effect of hundreds to thousands of potential compounds, under many different possible conditions, in tests carried out under automated or semi-automated regimes (43)(44)(45). Our fluorescent plate reader assay has demonstrated its utility to evaluate surfactant inhibition effects such as those produced by serum proteins like albumin (8,46). Deactivation of surfactant by serum components and by inflammatory mediators leaked into the alveolar spaces is thought to be a major determinant of the respiratory failure in acute respiratory distress associated with lung injury (16,47).…”
Section: Discussionmentioning
confidence: 99%
“…The search for new drugs of potential clinical interest directed to specific pathologically relevant targets is usually conducted through the analysis of the effect of hundreds to thousands of potential compounds, under many different possible conditions, in tests carried out under automated or semi-automated regimes (43)(44)(45). Our fluorescent plate reader assay has demonstrated its utility to evaluate surfactant inhibition effects such as those produced by serum proteins like albumin (8,46). Deactivation of surfactant by serum components and by inflammatory mediators leaked into the alveolar spaces is thought to be a major determinant of the respiratory failure in acute respiratory distress associated with lung injury (16,47).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent in vitro study under conditions resembling the exposure of surfactant to inhibitors in the lungs revealed that neither serum albumin nor fibrinogen were persistently inhibitory to pulmonary surfactant and normal near-zero minimum surface tension values were obtained after a small number of cycles (5). Moreover, there is evidence of protective effects of plasma proteins on surfactant inactivation.…”
mentioning
confidence: 80%
“…Previous studies have shown that cholesterol is an integral component of LS, found between 7-15 in various mammalian systems 9,10,39,43,44 . However, the physiological role of cholesterol is not clear to date, since the source of the material as well as its delivery route in LS has not been firmly established.…”
Section: Cholesterol and Lung Surfactantmentioning
confidence: 99%
“…In their study, minimal delay or rapid adsorption was noticed in BLES film formation with the presence of a pre-formed protein film. They concluded that surfactant inhibition was likely caused by a dysfunctional film instead of inhibition by way of competitive adsorption of the serum proteins 39 . This contradicted the previously reported result 11,17 .…”
Section: Serum Lipids and Proteinsmentioning
confidence: 99%
See 1 more Smart Citation